Exploring the motivations of mental health service utilization among family caregivers in Bolgatanga, Upper East Region, Ghana - Dennis B. Daliri; Gifty A. Aninanya; Timothy T. Laari; Nancy Abagye; Richard Dei‐Asamoa; Richard A. Afaya; Agani Afaya (Mental Health Science, 2024)
Abstract Family caregivers' role in sending their mentally ill relatives to the mental health service (MHS) has been vital in the era of community mental healthcare. They are the determinants of where mentally ill relatives are sent for care. There is currently no evidence about the motivators of MHS use among these major stakeholders in the Bolgatanga municipality. This study, therefore, sought to explore the perceived utilization and the motivating factors for the utilization of MHS in the Bolgatanga municipality. A descriptive qualitative study design was employed to conduct the study in two health facilities (Presbyterian Psychiatric Hospital and the Upper East Regional Hospital). A semi‐structured interview guide was used to conduct in‐depth interviews among 19 purposively sampled participants consisting of 15 family caregivers of mentally ill relatives, two MHS providers, and two MHS administrators. Audio‐recorded interviews were transcribed verbatim and thematically analyzed. Two main themes emerged including perceived utilization of MHS by family caregivers and motivating factors for the utilization of MHS. The study showed that most participants sought MHS for their mentally ill relatives. The study further identified multilevel factors such as individual factors, interpersonal factors, organizational factors, and policy‐level factors that motivated the utilization of MHS in the Bolgatanga municipality. There is a need to embark on activities that will further strengthen the factors that have been identified as motivators to encourage the continuous utilization of MHS in the municipality.